STUDI KEANEKARAGAMAN SPESIES NYAMUK ANOPHELES SP. DI KABUPATEN DONGGALA, PROVINSI SULAWESI TENGAH - Fahmi, Mohammad; Fahri, Fahri; Nurwidayati, Anis; Suwastika, I Nengah (Univ. Tadulako, 2014)
The aim of this study is to determine the diversity of morphological and genetic variation of the Anopheles sp. This study was conducted in the periode of November 2013 - February 2014 in two (2) malaria endemic areas; Labuan Village, in North Donggala and Lalombi Village, in South Banawa of South Donggala Regency. Sample collection was done around cattle cage throughout the night between 18:00 to 6:00. The capture period was 15 minutes oh each, and it was done in every hour. The collection was done by using an aspirator and the sampel was stored in paper cup prior covered by gauze pads. Morphological identification of samples was performed at Entomology Laboratory, Vector Borne Disease Research and Development Unit Donggala. Identification was done based on O'connor and Soepanto (1981). Analysis of genetic was done by RAPD-PCR method. Morphological identification found that there were three (3) species of mosquitoes from the two (2) sites, namely An. tesselatus, An. subpictus, and An. vagus. The highest spesies diversity index obtained in the Lalombi village with H' = 1,07 and the lowest value in the Labuan village with a value of H' = 0,33. RAPD analysis showed that there were similarity on DNA amplification band patterns on An. tesselatus from the village of Labuan and it from Lalombi. But interestingly, there were different on DNA amplification pattern of An. vagus from these two sites. This results indicating that the there was genetic variation on An. vagus from these two different villages, even though its have similarity in morphological characters.